2018
DOI: 10.1021/acssuschemeng.8b03587
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Free Method for the Copolymerization of Labile Sugar-Derived Building Blocks into Polyamides

Abstract: This research focuses on the preparation of biobased copolyamides containing biacetalized galactaric acid (GalX), namely, 2,3:4,5-di-O-isopropylidene-galactaric acid (GalXMe) and 2,3:4,5-di-O-methylene-galactaric acid (GalXH), in bulk by melt polycondensation of salt monomers. In order to allow the incorporation of temperature-sensitive sugar-derived building blocks into copolyamides at temperatures below the degradation temperature of the monomers and below their melting temperatures, a clever selection of sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…8 The synthesis of benzoxazine from the same biosourced products was also demonstrated, where performance polymers with glass transition temperatures (T g ) above 300°C and thermal stabilities exceeding 440°C. 9 Other examples of biosourced monomers include various sugars used in polycondensations and ring opening polymerisations, 10,11 dihydrolevoglucosenone and syrinaldehyde that have been used as a precursor for methacrylic monomers and in subsequent free radical polymerisations, 12,13 vanillin in cross-conjugated pyrrole-based polymers as well as in electrochemical reductive polymerisation to realise polyvanillin, 14,15 furfurylamine, which has been used to modify magnolol to synthesize benzoxazine for use as a thermosetting resin through ring opening polymerisation, 9 alloocimene polymerised through a redox emulsion process, 16 as well as carene- 8 and pinene-derived lactams for anionic polymerisation of polyamides, 17 and phellandrene-derived polyols used in polyurethane foam synthesis. 18 Of the aforementioned monomer classes and species, terpenes and terpenoids are some of the most promising and most commonly used, with utility in fragrances and perfumes, food, cosmetics, pharmaceuticals and even cigarettes and other inhalation products.…”
Section: Introductionmentioning
confidence: 99%
“…8 The synthesis of benzoxazine from the same biosourced products was also demonstrated, where performance polymers with glass transition temperatures (T g ) above 300°C and thermal stabilities exceeding 440°C. 9 Other examples of biosourced monomers include various sugars used in polycondensations and ring opening polymerisations, 10,11 dihydrolevoglucosenone and syrinaldehyde that have been used as a precursor for methacrylic monomers and in subsequent free radical polymerisations, 12,13 vanillin in cross-conjugated pyrrole-based polymers as well as in electrochemical reductive polymerisation to realise polyvanillin, 14,15 furfurylamine, which has been used to modify magnolol to synthesize benzoxazine for use as a thermosetting resin through ring opening polymerisation, 9 alloocimene polymerised through a redox emulsion process, 16 as well as carene- 8 and pinene-derived lactams for anionic polymerisation of polyamides, 17 and phellandrene-derived polyols used in polyurethane foam synthesis. 18 Of the aforementioned monomer classes and species, terpenes and terpenoids are some of the most promising and most commonly used, with utility in fragrances and perfumes, food, cosmetics, pharmaceuticals and even cigarettes and other inhalation products.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, stereochemistry has not been directly invoked in order to modulate properties in most of these examples. Synthetic polyamides possessing chiral centres are comparatively abundant and well represented in the literature with the stereochemistry usually derived from the use of naturally occurring comonomers and/or precursors, such as sugars [40][41][42][43][44][45][46][47][48] , amino acids 49,50 , tartaric acid [51][52][53] and terpenes [54][55][56] . A central feature among the stereo-defined polyamides is their inherent crystallinity, which has been assessed in most instances.…”
mentioning
confidence: 99%
“…A wide variety of acetal protective groups have been used to protect carbohydrate-based polyols prior to their polymerization, resulting in functional bio-based polymers with tunable properties [ 4 ]. For example, the incorporation of biacetilized mannarates, glucarates or galactarates into polymers elevates their glass transition region, suppresses crystallization of polymeric domains and lowers melting temperatures [ 5 , 6 ]. These properties can be translated to material properties and result in transparent polymers, which sustain their shapes at higher temperatures and simultaneously are easier to process due to their lower melting points.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, solvent-free polymer synthesis methods have received growing attention because of increasing environmental awareness and a greater focus on green chemistry principles [ 13 ], as well as economic aspects, e.g., the elimination of solvents and product isolation steps. Recent developments showed that in-melt polycondensation of cyclic acetal-bearing diacid monomers is possible if certain conditions are met [ 6 ]. Less substituted dioxolane-bearing molecules such as GalXH have been favored, due to their higher stabilities in acidic conditions.…”
Section: Introductionmentioning
confidence: 99%